(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
This paper contain analysis of principal stress isobars on a simple beam subjected to a three-point load. Analysis was conducted analytically using software Wolfram Mathematica and experimentally using reflection polariscope. Furthermore, working principle of polariscope is described and the preparation of samples for testing in reflective polariscope are shown. Comparison of results obtained analytically and experimentally are given as well as final conclusions and suggestions for further research.